Type II transmembrane serine proteases - Szabo, Roman; Wu, Qingyu; Dickson, Robert B.; Netzel-Arnett, Sarah; Antalis, Toni M.; Bugge, Thomas H. (Thrombosis and Haemostasis, 2003)
The recent availability of human and mouse genome sequences and expressed sequence tag databases facilitated the identification of a large new family of membrane anchored serine proteases, the type II transmembrane serine proteases or TTSPs. Analyses of human inherited disorders and gene targeting studies in mice have revealed that several members of this new protease family have critical functions in development and health. Preliminary studies also suggest that aberrant expression of type II transmembrane serine proteases may be linked to disease progression. The knowledge gathered thus far of the genetics, physiology, and pathology of this interesting new serine protease family will be reviewed here in brief.
Keywords: Serine proteases; cell surface proteolysis; transmembrane